Pembungkaman Pers Pada Masa Orde Baru (Refleksi Filosofis atas Kebebasan Pers Indonesia Masa Orde Baru) - Rr. Siti Murtiningsih; Joko Siswanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 1999)
The research wants to describe the condition of press stifling in the New Orde. Then, it tries make a philosophical reflection about the condition of arangement and practical standart of jurnalism in Indonesia post New Orde.The research uses the